2017
DOI: 10.3382/ps/pew298
|View full text |Cite
|
Sign up to set email alerts
|

Thermal manipulation during late embryogenesis: Effect on body weight and temperature, thyroid hormones, and differential white blood cell counts in broiler chickens

Abstract: The effects of thermal manipulation (TM) at 38.5°C and 40°C for 6 h at embryonic day (ED) 16, 9 h at ED 17, and 12 h at ED 18 on body weight (BW) and cloacal body temperature (T) during the first wk and later at post-hatch d 10, 14, 21, 28, and 42 were evaluated. Furthermore, chicks' ability to cope with a thermal challenge (TC; 41°C for 6 h) at post-hatch d 14 and 42 was also evaluated. A chick's response to TC was measured by determining the cloacal body temperature; the plasma thyroid hormones (thyroxin (T)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…Furthermore, to reduce metabolic heat production, peripheral T 3 is maintained low during high ambient temperature (Melesse et al 2011). Other reports have also described a significant drop in levels of T 3 and decreased metabolic rate in thermally conditioned chicken (Piestun et al 2011;Al-Zghoul et al 2015;Al-Rukibat et al 2017). The present observations differ from that of Rajkumar et al (2015a) where thermal manipulation did not alter the T 3 level chicken.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, to reduce metabolic heat production, peripheral T 3 is maintained low during high ambient temperature (Melesse et al 2011). Other reports have also described a significant drop in levels of T 3 and decreased metabolic rate in thermally conditioned chicken (Piestun et al 2011;Al-Zghoul et al 2015;Al-Rukibat et al 2017). The present observations differ from that of Rajkumar et al (2015a) where thermal manipulation did not alter the T 3 level chicken.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have previously shown that embryonic thermal manipulation (TM) could enhance adult poultry performance characteristics, such as thermoregulation during acute heat stress and breast muscle yield (Piestun et al, 2011(Piestun et al, , 2013Al-Rukibat et al, 2017). For the first time, we have shown that a moderate increase in incubation temperature during the second half of embryogenesis could improve foie gras production (by up to 15%) in adult male mule ducks.…”
Section: Discussionmentioning
confidence: 87%
“…the temperature variation, period and duration of the treatment (Collin et al, 2005;Piestun et al, 2008a;Loyau et al, 2013;Narinç et al, 2016;Al-Rukibat et al, 2017). Furthermore, most of the previous studies were conducted on chicken, raising the possibility that different species could respond differently to TM.…”
Section: Early Impact Of Embryonic Tmmentioning
confidence: 99%
“…Thermal manipulation ( TM ) during broiler embryogenesis, by increasing or decreasing the incubation temperature, was suggested to enhance heat tolerance during posthatch life ( Piestun et al., 2008 , Molenaar et al., 2010 , Al-Zghoul et al., 2013 , Al-Zghoul et al., 2015b , Al-Rukibat et al., 2017 ). Heat-tolerance improvement was achieved by the modulation of thyroid hormones, which are major players in the basal metabolic rate regulation, and HSP levels ( Al-Zghoul et al., 2013 , Al-Zghoul et al., 2015a , Al-Zghoul et al., 2015b , Al-Zghoul et al., 2015c , Al-Rukibat et al., 2017 ). Previously, TM was reported to increase Hsp70, HSF3, IL-1β, TNF-α, IL-6, TLR2, and TLR4 and to decrease catalase, GPX, SOD, and NOX expression in broiler chickens during acute heat stress ( Al-Zghoul et al., 2018 , Al-Zghoul et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%